2007
DOI: 10.1097/01.ta.0000219143.69483.71
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Plasma Adrenocorticotropin Hormone and Intensive Care Unit Survival in Early Traumatic Brain Injury

Abstract: The presence of a low plasma ACTH concentration at an early stage of TBI and lack of indication to provide second-level measures to control ICP were associated with a higher intensive care unit survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…However, at the current moment we agree with other authors that baseline cortisol values must be included in the definition of posttraumatic AI [7,10]. Therefore, we considered as diagnostic of AI the existence of baseline cortisol \5 lg/dl (7) or a delta cortisol after HDCST \9 lg/dl [8,12].…”
Section: Definition Of Posttraumatic Adrenal Insufficiencymentioning
confidence: 54%
See 4 more Smart Citations
“…However, at the current moment we agree with other authors that baseline cortisol values must be included in the definition of posttraumatic AI [7,10]. Therefore, we considered as diagnostic of AI the existence of baseline cortisol \5 lg/dl (7) or a delta cortisol after HDCST \9 lg/dl [8,12].…”
Section: Definition Of Posttraumatic Adrenal Insufficiencymentioning
confidence: 54%
“…Studies have shown contradictory results when reporting patients who are more likely to present adrenal impairment [4][5][6][7][8][9][10][11][12][13][14], and in most cases, the population of TBI patients studied was not homogeneous. Recent studies have also shown that HPA axis disturbances are common in trauma patients without TBI [15,16].…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations